Pengendalian Kualitas Produk Pakaian Bayi dengan Metode Statistical Quality Control - Amanda, Sheva; Suparno, Adizty (Institut Transportasi dan Logistik Trisakti, 2025)
Quality Control is a very important activity for the company to increase the market and income due to consumers’ highly consideration of the goods quality when purchasing. The purpose of the research is to determine the causes of rejected products and to provide solutions. The research was using Statistical Quality Control method which included process diagrams, check sheets, histograms, control charts, Pareto diagrams, scatter diagrams, Fishbone diagrams, and 5W+1H. The results show that there are two types of prioritized rejected products that are holes and dirty ones. Based on the data processing and calculation on the control map, there are several points outside the control limits caused by overheat machine used and human error. Based on the data processing carried out using Fishbone diagram, there are some factors causing these types of rejected goods of apparel such as operator negligence, lack of machine maintenance, poor quality of the materials, and insufficient lighting. The proposed improvements to be implemented are arranging supervision schedules, managing shift schedules, conducting daily briefings, scheduling the machine maintenance, selecting material vendors using AHP method, and re-arranging the production layouts. Kata kunci : Pengendalian Kualitas, Statistical quality control, Produk Reject